Lumbar Epidural Cavernous Hemangioma : A Case Report (Ibrahim Cardiac Medical Journal, 2019)
A 34 year smale patient presented with diffuse low-back pain with bilateral radiculopathy for 8 months duration.The magnetic resonance imaging showed an extradural space occupying lesion in spinal canal from L2 to L5 vertebral levels. The mass was well-marginated with bone involvement. Radiological diagnosis was questionable. The patient underwent L2 to L5 laminectomy under general anesthesia. Intraoperatively, the tumor was purely extradural in location with devoid of attachment to the nerves or dura. Total excision of the extradural compressing mass was not possible due to high vascularity. Histopathology revealed cavernous hemangioma. Purely epidural hemangiomas are uncommon and should be considered in the differential diagnosis of spinal epidural soft tissue masses. Findings that may help differentiate this lesion from the disk prolapse include more common meningiomas and nerve sheath tumors. Early diagnosis and complete removal is the treatment of choice.Ibrahim Card Med J 2018; 8 (1&2): 71-73